In Vitro Hematological and In Vivo Vasoactivity Assessment of Dextran Functionalized Graphene - Chowdhury, Sayan Mullick (Nature Publishing Group, 2013)
The intravenous, intramuscular or intraperitoneal administration of water solubilized graphene nanoparticles for biomedical applications will result in their interaction with the hematological components and vasculature. Herein, we have investigated the effects of dextran functionalized graphene nanoplatelets (GNP-Dex) on histamine release, platelet activation, immune activation, blood cell hemolysis in vitro, and vasoactivity in vivo. The results indicate that GNP-Dex formulations prevented histamine release from activated RBL-2H3 rat mast cells, and at concentrations ≥ 7 mg/ml, showed a 12–20% increase in levels of complement proteins. Cytokine (TNF-Alpha and IL-10) levels remained within normal range. GNP-Dex formulations did not cause platelet activation or blood cell hemolysis. Using the hamster cheek pouch in vivo model, the initial vasoactivity of GNP-Dex at concentrations (1–50 mg/ml) equivalent to the first pass of a bolus injection was a brief concentration-dependent dilation in arcade and terminal arterioles. However, they did not induce a pro-inflammatory endothelial dysfunction effect.